Single‐port versus conventional laparoscopic distal pancreatectomy: a propensity score matched analysis and a learning curve of single‐port approach. (18th July 2019) - Park, Pyoungjae; Han, Hyung Joon; Song, Tae‐Jin; Choi, Sae Byeol; Kim, Wan‐Bae; Yoo, Young Dong; Kim, Dong‐Sik; Cha, Jae Hyung
Abstract: Background: Single‐port laparoscopic approaches are well established in the field of minimally invasive surgery; however, single‐port laparoscopic distal pancreatectomy (SPLDP) has not been evaluated in a large number of distal pancreatic neoplasms. We aimed to compare single‐port laparoscopic distal pancreatectomy outcomes with conventional laparoscopic distal pancreatectomy (LDP) outcomes. Methods: We retrospectively evaluated the medical records of 101 patients who underwent SPLDP ( n = 26) or LDP ( n = 75). We performed 1:1 propensity score matching between the two groups. Consequently, 26 patients were included in each group. We analyzed the learning curve based on the operation time in SPLDP. Results: Single‐port laparoscopic distal pancreatectomy could be performed with fewer trocars ( P < 0.001) and assistants ( P < 0.001). However, compared to the LDP group, mean operation time was longer (278.9 vs. 178.7 min, P < 0.001) and splenic vessel preservation rates were lower (0% vs. 46.2%, P < 0.001) in the SPLDP group. The mean pain visual analogue scale score was significantly lower at postoperative day 1 ( P < 0.001) and day 2 ( P < 0.001) in the SPLDP group. The learning curve was determined in the 12th case for SPLDP. Conclusions: Single‐port laparoscopic distal pancreatectomy is comparable in safety to conventional laparoscopic approaches for distal pancreatic neoplasms, with fewer trocars, assistants and less pain; however, operation time was longer. Abstract : Highlight Although single‐port laparoscopic approaches are well established in the field of minimally invasive surgery, single‐port laparoscopic distal pancreatectomy has not been evaluated in a large number of cases. Park and colleagues demonstrated that single‐port laparoscopic distal pancreatectomy offers several advantages and is comparable in safety to conventional laparoscopic approaches.